Semantic knowledge network inference across a range of stakeholders and communities of practice. (November 2018) - Alexandridis, Kostas; Takemura, Shion; Webb, Alex; Lausche, Barbara; Culter, Jim; Sato, Tetsu
Abstract: This paper provides empirical and experimental assessments of thematic knowledge discourses based on two case studies in the US Virgin Islands and Florida. We utilize a latent semantic indexing analysis over natural language corpus to classify and categorize knowledge categories. We computed TF*IDF scores and associated co-occurrence Jaccard similarity scores to construct semantic knowledge networks. Using network analysis, we computed structural metrics over four composite groups: neighbor-based, centrality, equivalence and position. The analysis show that structural network characteristics of environmental knowledge can exponentially predict associations between knowledge categories. We show that connectivity play a critical role on acquisition, representation, and diffusion patterns of knowledge within local communities. We provide evidence of a global prevalence of a shared knowledge core. We show that core social-ecological attributes of knowledge follow scale-free, power law distributions and stable, equilibrium network structures. We identify two distinct models of bidirectional translation: a bottom-up and a top-down. Highlights: Analyzes the structure and characteristics of integrated local environmental knowledge in terms of semantic network analysis. Critically examines similarities and differences in knowledge self-organization across social groups and locations. Addresses semantic network neighbor, centrality, equivalence and positional characteristics in terms of semantic knowledge extraction. Provides evidence of scale-free distribution of environmental knowledge. Identifies knowledge transformations in terms of social-ecological complexity and the social understanding of reality. Provides a comprehensive structural analysis of the hierarchical structure of integrated environmental knowledge networks.